The Paradox of Quantum Information and Its Ethical Consequences - Possati, Luca (Scenari, 2023)
This paper explores the impact of the measurement problem in quantum mechanics on quantum information theory. It intends to see whether Floridi’s theory of information can be appropriately extended or adapted to the quantum domain. The claim is that it doesn’t seem possible for Floridi’s theory to be applied to quantum systems because it requires a process of validation whose requirements are incompatible with quantum mechanics. The second section of the paper analyzes the notion of semantic information through the lens of Floridi’s theory of semantic information. The third section examines the problem of semantic information in quantum computing. This section is divided into two parts. The first gives an elementary description of the measurement problem. The second part shows how in the quantum field the veridicality thesis, that is, the core of Floridi’s approach, fails. The fourth section investigates the ethical consequences of this thesis. These consequences mainly concern the opacity of quantum algorithms, that is, their lack of transparency and the difficulty of explaining and justifying their decisions.